Pembuatan Desain Kemasan dan Logo Menggunakan Aplikasi Coreldraw sebagai Strategi Pemasaran Melalui Rebranding di UMKM Rosya Kab. Malang - Rizki Ira Sindi; Umi Khabibah; Dwi Sudjanarti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Based on observations made at Rosya Singosari MSME in Malang Regency, the products sold, namely traditional herbal powder, are only packaged simply using standing pouch packaging with stickers on it. In addition, the logo owned by Rosya also seems sober and does not describe the MSME and its product. The purpose of this research is to rebrand the packaging and logo design, so that the packaging can be more attractive and the logo can describe the identity of MSME using the CorelDRAW application. The research method used was the action research method with procedures consisting of planning, action, observation, and reflection. The data collection methods were observation, interviews, questionnaires, and documentation. The packaging and logo design that have been completed were then tested by distributing questionnaires to 21 respondents including, 1 business owner, 1 employee, 2 design experts, 2 marketing experts and 15 respondents. The measurement of the effectiveness of design development was measured using the EPIC method (Emphaty, Persuation, Impact, Communication). The results of distributing questionnaires showed that the packaging and logo design included in the very effective category as evidenced by the results of the EPIC Rate calculation which get a value of 4.5 and 4.3. The conclusion of this study indicates that the new packaging and logo design are suitable for use in Rosya as a replacement for the old packaging and logo. Suggestion that can be given to Rosya is to use a new design in order to expand the market reach and to attract more consumers.